2008
DOI: 10.12968/ajmw.2008.2.3.30713
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to intermittent preventive treatment for malaria in pregnancy

Abstract: Malaria during pregnancy is a serious health risk for pregnant women; it is associated with maternal and infant morbidity and mortality. In Uganda, Intermittent Preventive Treatment (IPT) for prevention of Malaria in pregnancy, coverage one and two are still low standing at 61%, 38% respectively. To identify client-related, health worker-related and health-related factors affecting adherence to IPT. A descriptive cross-sectional study involving 222 pregnant women and 15 health workers was undertaken in Kampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This study result is not different from results of other studies which reported that knowledge of IPTp is significantly related to uptake of IPTp [ 19 , 21 , 23 ]. It is therefore not surprising that studies that reported low level of knowledge of IPT among pregnant women resulted in low uptake of IPTp [ 24 ]. This probably explains why health education among pregnant women on IPTp will better improve their knowledge level and increase uptake.…”
Section: Discussionmentioning
confidence: 99%
“…This study result is not different from results of other studies which reported that knowledge of IPTp is significantly related to uptake of IPTp [ 19 , 21 , 23 ]. It is therefore not surprising that studies that reported low level of knowledge of IPT among pregnant women resulted in low uptake of IPTp [ 24 ]. This probably explains why health education among pregnant women on IPTp will better improve their knowledge level and increase uptake.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, [17] found that only 21% of the participants had received information about IPTp, of which only 31.5% knew the recommended drugs for IPTp and only 4.5% knew the recommended dose. The study found that over 60% of the participants did not receive health education on IPTp, resulting to low IPTp coverage [17].…”
Section: Factors Influencing the Uptake Of Intermittent Preventive Trmentioning
confidence: 97%
“…In their study, [17] found that only 21% of the participants had received information about IPTp, of which only 31.5% knew the recommended drugs for IPTp and only 4.5% knew the recommended dose. The study found that over 60% of the participants did not receive health education on IPTp, resulting to low IPTp coverage [17]. Other studies such as [18] and [19] also confirm that knowledge about IPTp remains low among pregnant women in developing countries, which suggests that ANC facilities are not doing enough on sensitization.…”
Section: Factors Influencing the Uptake Of Intermittent Preventive Trmentioning
confidence: 97%